2009
DOI: 10.1136/emj.2007.053298
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of mortality in adult emergency department patients with sepsis

Abstract: These results demonstrate the efficacy of the abbreviated MEDS score, the MEW score and NPT venous lactate levels in predicting 28-day mortality in ED patients with sepsis. The abbreviated MEDS score was found to be the best performing risk assessment model which, with prospective validation, may aid early clinical decision-making in ED patients with sepsis and might affect the outcome from sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
2
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 21 publications
(29 reference statements)
4
81
2
2
Order By: Relevance
“…20 Where the precise FiO 2 was not known, this was estimated from the inspired oxygen concentration and device, according to Data Supplement S4 (available as supporting information in the online version of this paper). For the MEDS score, neutrophil bands were excluded as described by Vorwerk et al 21 since these are not reported by our laboratory. Finally, the PIRO model was modified to use blood urea > 8 mmol/L to replace blood urea nitrogen (BUN) > 20 mg/dL, and again neutrophil bands could not be included in the score.…”
Section: Study Protocolmentioning
confidence: 99%
“…20 Where the precise FiO 2 was not known, this was estimated from the inspired oxygen concentration and device, according to Data Supplement S4 (available as supporting information in the online version of this paper). For the MEDS score, neutrophil bands were excluded as described by Vorwerk et al 21 since these are not reported by our laboratory. Finally, the PIRO model was modified to use blood urea > 8 mmol/L to replace blood urea nitrogen (BUN) > 20 mg/dL, and again neutrophil bands could not be included in the score.…”
Section: Study Protocolmentioning
confidence: 99%
“…The MEDS score also correlated well with the classification of clinical severity of sepsis [24]. The abbreviated MEDS score evaluated by Vorwerk et al was found to have a better performance as a predictor of 28-day mortality (AUC = 0.81) when compared to serum lactate (AUC = 0.62) among patients enrolled from the urban teaching centre [26]. A MEDS score of 13 and above was found to correlate well with those with severe sepsis and septic shock with a specificity of 85.3%, PPV of 70.4%, and NPV of 79.5% by Zhao et al [25].…”
Section: Outcomementioning
confidence: 84%
“…of nine (without the neutrophil bands) [26]. Zhao et al also assessed the impact on the prognostic value of the MEDS score by combining it with one of the biomarkers [25].…”
Section: Prognostic Determinant and Comparatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that this is an important consideration that should be addressed by future prospective study. Finally, this study did not address clinical changes after index lactate values (e.g., incident hypotension or organ failure) that might have altered lactate values or fluid administration practice independently of our observed variables (14,18,29,41).…”
Section: Discussionmentioning
confidence: 99%